Analysis Study About House Renovation Program Implementation of the Pasaman Regency BAZNAS from 2020 to 2022 - Lendrawati, Lendrawati; Warsah, Idi; Amin, Ibnu (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The problem in this study is how to implement the home renovation program carried out by BAZNAS in Pasaman Regency and see how effective it is. The study used qualitative methods, to collect data and information by means of observation and interviews. Processing the data used a qualitative descriptive analysis method, namely explaining the data without using calculations, doing reasoning, analyzing, and responding to actual facts. The results of the research, implementation of the home renovation program, namely BAZNAS composes, makes programs and budgets for home renovations. Mustahik candidates must complete the requirements made by BAZNAS. Each mustahik gets Rp. 15,000,000.00, of the funds mustahik must be good at managing the funds given. BAZNAS did not specify the shape of the house to be built. From 2020 to 2022, there are still nine mustahik recipients of program assistance who have not used the funds provided. The reason mustahik has not dared to build a house with such large funds. Judging from its effectiveness, BAZNAS has not been effective in carrying out home renovation programs. Program formulation that has not been achieved, also its achievements have not been effective, supervision and control that does not exist, transparency and review are not under control. As a result, it is not known whether mustahik has used the funds given to renovate the house.